THE APPRAISAL OF BIAS AND POWER AS EXPRESSED IN SEVERAL INDONESIAN NEWS ARTICLES ABOUT INDONESIA NEW HOUSE SPEAKER INAUGURATION - Ismi Kuntum Zulaikha; Sabta Diana (Fakultas Ilmu Budaya Universitas Jember, 2017)
Abstract This research discusses about bias and power in the four chosen news articles published by the Jakarta Post. Those four articles discuss the competition between two bickering factions inside Golkar Party, Bakrie’s group and Laksono’s group, to grab the position of new house speaker in early 2016. The main goal of this research is to reveal the power and bias applied implicitly through the linguistic features enacted in media. The revelation of bias is analyzed through its linguistic choice by using Appraisal theory proposed by Martin and White (2005). Since bias is one of the social inequalities phenomena, this research is revealed under Critical Discourse Analysis (CDA) scope, especially using Firclough’s three dimensional frameworks, which deals with analyzing the relation between language and social context. The Jakarta Post needs to obey the principles of journalist that are being neutral, independent and objective in informing the news. However, the result of this research shows that the media is possible to do bias because of political interest.